Rapid prototyping of a modular optical flow cell for image-based droplet size measurements in emulsification processes - Burke, Inga; Assies, Christina; Kockmann, Norbert (Journal of flow chemistry, 2024)
Emulsification processes are often found in the process industry and their evaluation is crucial for product quality and safety. Numerous methods exist to analyze critical quality attributes (CQA) such as the droplet sizes and droplet size distribution (DSD) of an emulsification process. During the emulsification process, the optical process accessibility may be limited due to high disperse phase content of liquid-liquid systems. To overcome this challenge, a modular, optical measurement flow cell is presented to widen the application window of optical methods in emulsification processes. In this contribution, the channel geometry is subject of optimization to modify the flow characteristics and produce high optical quality. In terms of rapid prototyping, an iterative optimization procedure via SLA-3D printing was used to increase operability. The results demonstrated that the flow cell resulting from the optimization procedure provides a broad observation window for droplet detection. Graphical abstract